Ubuntu as Social Ethics - Eyesan, Solomon (Conatus - Journal of Philosophy, 2025)
This paper explores the indigenous African philosophy of Ubuntu and its implications as both a worldview and social ethics. It argues that Ubuntu not only describes the African understanding of personhood, emphasizing connectedness, interdependency, and relatedness, but also prescribes a moral framework grounded in principles such as identity, solidarity, tolerance, justice, respect, compassion, and human dignity. By clarifying Ubuntu’s principles and differentiating it from related concepts such as community, communalism, communism, and communitarianism, the paper addresses the following key questions: What is Ubuntu? How does it differ from similar concepts? What values define Ubuntu? Can Ubuntu contribute meaningfully to global ethical discourses? This paper significantly dwells on the individual-community debate within the context of Ubuntu philosophy, arguing that Ubuntu philosophy offers a compelling ethical alternative in the face of the prevailing dominant social paradigm of exploitation, oppression, hatred, division, religious conflicts, terrorism, and intolerance at the local and international levels.